2022
DOI: 10.1093/europace/euac014
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of sudden cardiac death in arrhythmogenic right ventricular cardiomyopathy: a pooled analysis

Abstract: Aims Arrhythmogenic right ventricular cardiomyopathy (ARVC), an inherited heart muscle abnormality, is a major cause of sudden cardiac death (SCD). However, the burden of SCD and risk factors in ARVC are not clearly described. Thus, we estimated the rates and predictors of SCD in ARVC in a meta-analysis. Methods and results PubMed, Embase, and Web of Science were searched through 7 April 2021. Prospective studies reporting SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
17
0
2
Order By: Relevance
“…RV fractional area change <23%), male sex, T-wave inversion, QRS dispersion, non-sustained VT and LV dysfunction have been associated with an increased risk of life-threatening ventricular arrhythmias and SCD. 221,222 Risk assessment models have been proposed for predicting the risk of life-threatening ventricular arrhythmias (including SCD), 223,224 however their practical use requires further validation. 225 Recently, a risk prediction model to estimates the 5-year risk of incident ventricular arrhythmias in ARVC has been developed (ARVCrisk.…”
Section: Arrhythmogenic (Right Ventricular) Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation
“…RV fractional area change <23%), male sex, T-wave inversion, QRS dispersion, non-sustained VT and LV dysfunction have been associated with an increased risk of life-threatening ventricular arrhythmias and SCD. 221,222 Risk assessment models have been proposed for predicting the risk of life-threatening ventricular arrhythmias (including SCD), 223,224 however their practical use requires further validation. 225 Recently, a risk prediction model to estimates the 5-year risk of incident ventricular arrhythmias in ARVC has been developed (ARVCrisk.…”
Section: Arrhythmogenic (Right Ventricular) Cardiomyopathymentioning
confidence: 99%
“…Unexplained (arrhythmic) syncope, 218,220 severe RV dysfunction (e.g. RV fractional area change <23%), male sex, T‐wave inversion, QRS dispersion, non‐sustained VT and LV dysfunction have been associated with an increased risk of life‐threatening ventricular arrhythmias and SCD 221,222 . Risk assessment models have been proposed for predicting the risk of life‐threatening ventricular arrhythmias (including SCD), 223,224 however their practical use requires further validation 225 .…”
Section: Arrhythmogenic (Right Ventricular) Cardiomyopathymentioning
confidence: 99%
“…111,112 A meta-analysis of 52 cohort studies (total of 5485 ARVC patients) reported the incidence of SCD of ∼0.7% per year in ARVC patients without ICD, and a significantly lower SCD incidence (0.65 per 1000 patients per year) in ICD recipients. 113…”
Section: Arrhythmogenic Right Ventricular Cardiomyopathy Incidence An...mentioning
confidence: 99%
“…Disease penetrance in family members is ∼30% and positive genetic testing identifies individuals at higher risk of developing ventricular arrhythmias 125 . However, there are conflicting data on an independent predictive value of genetic basis for SCD in ARVC 113 . It is noteworthy that certain non‐desmosomal mutations (e.g.…”
Section: Arrhythmogenic Right Ventricular Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation